1975
DOI: 10.1111/j.1348-0421.1975.tb00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Materials for γ Phage Adsorption to the Cell Wall of Bacillus anthracis, Strain Pasteur No. 2‐H

Abstract: Cell wall preparations of Bacillus anthracis, strain Pasteur No. 2‐H, were treated with heat or with acetone and ether. Both of the treated cell walls preparations inactivated γ phage. The centrifuged supernatant of the heat‐treated cell walls was fractionated on Sephadex G‐200, and four fractions containing reducing sugars were obtained. The first fraction had the phage‐inactivating activity. On the other hand, the fourth fraction had no phage‐inactivating activity, but strongly inhibited phage adsorption to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ␥ phage receptor is probably a cell wall-associated protein. Indeed, some of the substances described as determinants of the phage receptor site are constituents of the peptidoglycan or of the associated polysaccharide (23,44). To identify the ␥ phage receptor, we assayed the resistance of B. anthracis mutants deficient in cell wall protein anchoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ␥ phage receptor is probably a cell wall-associated protein. Indeed, some of the substances described as determinants of the phage receptor site are constituents of the peptidoglycan or of the associated polysaccharide (23,44). To identify the ␥ phage receptor, we assayed the resistance of B. anthracis mutants deficient in cell wall protein anchoring.…”
Section: Resultsmentioning
confidence: 99%
“…Lantos and Ivanovics reported that ␥ phage binding was lost after a treatment with 5% trichloracetic at 90°C and then trypsin, suggesting that the receptor might be a protein (15). Watanabe and Shiomi suggested that one or a combination of the following substances, meso-Dap, D-glucosamine, D-galactosamine, D-mannosamine, constituents of the peptidoglycan or the associated polysaccharide (23), and L-lysine, constitute the phage receptor site (44). They excluded the protein hypothesis due to maintenance of phage binding after solvent treatment.…”
mentioning
confidence: 99%